Human Capital Return-on-Investment (HCROI) in South African companies listed on the Johannesburg Stock Exchange (JSE) - Viljoen, Hendrina Helena (Stellenbosch : Stellenbosch University, 2012)
Thesis (MComm)--Stellenbosch University, 2012.